Nano-Fe3O4@silica sulfuric acid as a reusable and magnetically separable potent solid acid catalyst in Biginelli-type reaction for the one-pot multicomponent synthesis of fused dihydropyrimidine derivatives: A greener NOSE and SFRC approach. Issue 3 (1st February 2016) - Dam, Binoyargha; Pal, Amarta Kumar; Gupta, Ajay
ABSTRACT: An efficient, highly product selective, eco-friendly, one-pot multicomponent synthesis of dihydropyrimidine derivatives via Biginelli reaction has been described. The reaction was developed by greener nanoparticle-catalyzed organic synthesis enhancement (NOSE) chemistry and solvent free reaction condition (SFRC) approaches, which helped us in making the procedure greener. The reaction went smoothly with a diverse range of aromatic, aliphatic, hetero-aromatic aldehydes, different amine sources, as well as variousβ -dicarbonyl compounds, showing the flexibility of this methodology. Magnetically separable nano-Fe3 O4 @SiO2 @SO3 H, which acts as a potent solid acid catalyst, was characterized by FT-IR, SEM, EDX and TEM, VSM, and TGA analyses. The catalyst was recycled from the reaction mixture easily by an external magnet and reused in five more consecutive runs without much decrease in catalytic activity. Its catalytic efficiency was compared to other nano and bulk solid acid catalyst in order to ascertain the best combination for the conversion. GRAPHICAL ABSTRACT: